Nursing care for heart failure patients and related factors at Hanoi Heart Hospital in 2024 - Nguyen, Thi Thu Phuong; Vu, Quynh Nga; Bach, Thi Hoa; Le, Thi Thanh Binh; Pham, Thi Hong Thi (Tạp chí Y học Thảm hoạ và Bỏng, 2024)
Objective: To assess the nursing care quality and some factors related to the outcome of care for hospitalized heart failure patients at Hanoi Heart Hospital in 2024. Method: We performed a cross-sectional study evaluating 21 routine nursing care activities for the level of completion on three days: day 1, day 3, and the day of discharge. We also identified the relevant factors to the patient care outcome. The data was collected from medical records and patient interviews. Results: Among the total of 156 hospitalized heart failure patients participating in the study, 83.3% of patients received good nursing care at the hospital, while only 16.7% of heart failure patients did not receive adequate nursing care. Factors related to the outcome of patient care include: Age group, gender, socioeconomic status, number of hospitalizations per year, disease duration, and patient satisfaction. (p < 0.05). Conclusion: Proper nursing care for hospitalized.